Strategi Lobi dan Negosiasi Dalam Proses Komunikasi Politik - Suci Ramadhani; Jihan Hana Nasution; Mhd Irsyad Azhari; Winda Kustiawan (JURNAL EDUKASI NONFORMAL, 2022)
The practice of lobbying and negotiation is often seen as the involvement of conflict in politics. A number of negotiation activities, for example, in the process of merging political interests ranging from policy making, coalitions, fusions, alliances to confederations, require negotiation. Likewise, during a conflict, for example, during a border conflict between a country, one of the solutions to cases like this is through negotiation. Ordinary people in general will perceive the practice of lobbying and negotiation as something negative. But actually negotiation can be interpreted as talking with other people with the intention of reaching an agreement and the goals of both parties. The practice of lobbying and negotiation is usually used by legislators as a form of political communication. For that we need the right strategy in lobbying and negotiating. By using descriptive qualitative research, the authors access the data by describing or describing the collected data related to lobbying and negotiation strategies in the political communication process. So that the author can draw the conclusion that the practice of lobbying and negotiation can be carried out by means of a distributive approach (win-lose approach), a lose-lose approach, a compromise approach, and an integrative approach (win-win approach).